Pengaruh Globalisasi Dalam Bidang Pembangunan Ekonomi Dan Pelestarian Lingkungan - Dicky Ahmad Fahrizi; Kartika Novita Rohmah; Rheihan Alvizar (Journal of Management and Creative Business, 2023)
Globalization has become an important phenomenon in economic development and environmental preservation. This article aims to investigate the influence of globalization on these two important aspects, namely economic development and environmental preservation. In the context of economic development, globalization has provided significant opportunities and challenges. In recent years, globalization has opened the door for countries to engage in broader international trade, foreign direct investment, and technology transfer. The empirical studies conducted in this article show that countries that have been able to capitalize on these opportunities have experienced rapid economic growth. However, globalization can also create economic disparities between countries and increase the risk of vulnerability to global economic crises. Therefore, wise management of globalization becomes very important to achieve sustainable economic development. In addition, globalization also has a significant impact on environmental preservation. Globalization facilitates the exchange of goods and services across national borders, but it also accelerates the process of uncontrolled exploitation of natural resources. This article examines the relationship between globalization and environmental degradation, focusing on deforestation, pollution and climate change. Case studies show that increased international trade has had a negative impact on ecosystems and biodiversity in several regions. However, this article also identifies strategies that can be adopted to promote sustainable economic development and environmental preservation in tandem, such as stringent environmental policies, green technology innovation, and international cooperation. Thus, this article concludes that globalization has a complex influence in the field of economic development and environmental preservation. While globalization can provide significant economic opportunities, the challenges of managing its negative impact on the environment must also be addressed effectively. The integration of economic development policies and environmental preservation is the key to achieving sustainable growth and ecological balance in the era of globalization